Spatial Updating Depends on Gravity - Stahn, Alexander Christoph; Riemer, Martin; Wolbers, Thomas; Werner, Anika; Brauns, Katharina; Besnard, Stephane; Denise, Pierre; Kühn, Simone; Gunga, Hanns-Christian (Frontiers in Neural Circuits, 2020)
As we move through an environment the positions of surrounding objects relative to our body constantly change. Maintaining orientation requires spatial updating, the continuous monitoring of self-motion cues to update external locations. This ability critically depends on the integration of visual, proprioceptive, kinesthetic, and vestibular information. During weightlessness gravity no longer acts as an essential reference, creating a discrepancy between vestibular, visual and sensorimotor signals. Here, we explore the effects of repeated bouts of microgravity and hypergravity on spatial updating performance during parabolic flight. Ten healthy participants (four women, six men) took part in a parabolic flight campaign that comprised a total of 31 parabolas. Each parabola created about 20–25 s of 0 g, preceded and followed by about 20 s of hypergravity (1.8 g). Participants performed a visual-spatial updating task in seated position during 15 parabolas. The task included two updating conditions simulating virtual forward movements of different lengths (short and long), and a static condition with no movement that served as a control condition. Two trials were performed during each phase of the parabola, i.e., at 1 g before the start of the parabola, at 1.8 g during the acceleration phase of the parabola, and during 0 g. Our data demonstrate that 0 g and 1.8 g impaired pointing performance for long updating trials as indicated by increased variability of pointing errors compared to 1 g. In contrast, we found no support for any changes for short updating and static conditions, suggesting that a certain degree of task complexity is required to affect pointing errors. These findings are important for operational requirements during spaceflight because spatial updating is pivotal for navigation when vision is poor or unreliable and objects go out of sight, for example during extravehicular activities in space or the exploration of unfamiliar environments. Future studies should compare the effects on spatial updating during seated and free-floating conditions, and determine at which g-threshold decrements in spatial updating performance emerge.